Effect of Cryopreservation Using Slow Freezing or Vitrification on Viability and Metabolic Activity of Mesenchymal Stromal Cells Encapsulated Within Alginate Spheres with Diameter of 1 mm and More - Zaikov, Vedeney S.; Petrenko, Yuriy A.; Trufanova, Natalia A.; Pravdyuk, Aleksey I.; Volkova, Natalia A.; Mazur, Svetlana P.; Petrenko, Aleksandr Y. (Problems of Cryobiology and Cryomedicine, 2014)
The aim of the study was to evaluate the effect of exposure duration of alginate encapsulated mesenchymal stromal cells (MSCs) in multicomponent cryoprotective solution DEPS-1 (10% dimethyl sulfoxide, 20% ethylene glycol, 1,2-propane diol and 0.5 M sucrose) on survival and metabolic activity following cryopreservation using vitrification. The spheres of 1mm diameter obtained by dropwise addition of sodium alginate into calcium chloride were used in the experiments. Alginate spheres derived by this method contained more cells as compared to the spheres of (0.5 Â± 0.2) mm derived by pulverizing the alginate into calcium chloride. It was shown that using of multicomponent cryoprotective solution DEPS-1 allowed achieving successful cryopreservation of MSCs encapsulated in alginate spheres of different sizes. It was found that saturation with cryoprotective solution of MSCs encapsulated in spheres with 1.2 mm size needed a longer exposure with CPA if compared with spheres of 0.6 mm size. Probl Cryobiol Cryomed 2014; 24(3):222-230.